Clinical utility and safety of finerenone in patients with heart failure: Rationale and design of FINE registry - Gonzalo Luis Alonso Salinas; Amaia Martínez León; Diego Aguiar Cano; Alberto Esteban‐Fernández; José María Viéitez Flórez; Susana delPrado Díaz; Juan Górriz‐Magaña; Gregorio deLara Delgado; Rafael González‐Manzanares; Pedro Caravaca‐Pérez; Francisco J. Pastor‐Pérez; Sandra Valdivieso‐Moré; et al. (ESC Heart Failure, 2025)
Abstract Aims Information about current use of finerenone in patients with heart failure (HF) finerenone in clinical practice is scarce, and its effectiveness in clinical practice in patients is scarce. We aim to assess both the baseline clinical profile and prognostic role of finerenone in patients with HF, irrespective of ejection fraction. Methods and results The study is a multicentre, observational registry, including regional and tertiary hospitals. The registry incorporates contributions from cardiology, internal medicine, and nephrology departments, ensuring comprehensive data collection. Patients with previous history of decompensated HF and elevated natriuretic peptides (NPs) will be included and classified into two groups: Those initiating finerenone will constitute the study cohort, with a 1:1 matched control cohort including those patients not receiving finerenone. Follow‐up will occur at 6 and 12 months (and optional 3 and 5 years). Endpoints will include the incidence of HF exacerbations requiring intravenous therapy, hospitalizations, renal replacement therapy, and mortality due to cardiovascular or renal causes. Conclusions This study will provide valuable real‐world evidence on the clinical effectiveness and safety of finerenone across a wide range of HF patients, including those with reduced, mildly reduced, and preserved ejection fraction. By leveraging a large, representative, and controlled cohort, the findings aim to enhance clinical decision‐making and optimize the use of finerenone in routine practice, particularly in high‐risk patients with complex co‐morbidities.